The Prosody of Arabic Interrogative Speech (An Acoustic Phonetic Study) - Mutmainnah, Salma; Al Farisi, Mohamad Zaka; Saleh, Nalahuddin; Langguly, Azra Adrina (Institut Agama Islam Negeri Palopo, 2024)
Prosody provides essential information regarding intonation, emotion, and the physiological characteristics of speakers. In communication, dialects often influence the intonation patterns used in interrogative utterances. This study aims to analyze the prosody of Arabic spoken by native and non-native speakers, using an acoustic-phonetic approach in a case study involving gender and ethnic variations between Sundanese and Javanese speakers, which have been underexplored in previous research. The prosodic features in this study are limited to pitch frequency, duration, and speech intensity. The data consists of two yes/no interrogative sentences analyzed using Praat software version 6.4.13. The results reveal differences in speech duration between native and non-native speakers, with native speakers exhibiting shorter durations. Regarding pitch contours, Javanese male speakers produce relatively flat frequencies at the end of sentences. Additionally, Sundanese female speakers demonstrate the lowest intensity among the participants. This study contributes to a deeper understanding of Arabic prosody in native and non-native speakers, serves as a reference for developing contextual teaching methods for non-native learners in Indonesia, and enriches the literature on acoustic phonetics in the context of ethnic differences in language speakers.